The History of Islamic Civilization: A Critical Review of the Thoughts of Ahmad Syalabi and A. Malik Fadjar in the Context of Islamic Education - Arsyada, Aziz Rizqi; Ali, Mohamad; Azani, Mohammad Zakki (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This paper critically examines the Islamic civilization from two distinctive yet complementary perspectives: Ahmad Syalabi's historical approach and A. Malik Fadjar's educational reorientation framework. Ahmad Syalabi provides a comprehensive historical narrative of Islamic civilization, emphasizing the periodization and cultural achievements of Muslim societies. Meanwhile, A. Malik Fadjar offers a progressive educational paradigm through his concept of "Reorientasi Pendidikan Islam," which integrates traditional Islamic values with modern educational needs. This study employs a qualitative library research method to synthesize both perspectives and their implications for contemporary Islamic education, particularly within the Muhammadiyah context. The findings reveal that understanding Islamic civilization through historical lenses while simultaneously embracing educational innovation represents a balanced approach toward achieving "Islam Berkemajuan" (Progressive Islam) in the 21st century.